AKULTURASI DALAM ARSITEKTUR RUMAH TINGGAL LASEM : Studi Kasus Rumah Liem King Siok - M. Maria Sudarwani; Edi Purwanto; Siti Rukhayah (Sabda: Jurnal Kajian Kebudayaan, 2018)
Lasem was called “La Petit Chinois” or “Small China” because there were Chinese community settlements consisting of old Chinese-style houses. Lasem was a large port city since the time of the Majapahit Kingdom until the Dutch colonialism encouraged cultural acculturation. Lasem batik is one of the results of acculturation of Javanese and Chinese culture and has been a noble outfit since King Lasem I ruled (1350-1375). Cultural acculturation forms a distinctive cultural identity that is an important part of coastal culture. Therefore the uniqueness of cultural acculturation in Lasem is interesting to study. The purpose of this study was to obtain an overview of Chinese residential architecture in Lasem Chinatown and Chinese culture in Lasem, so as to enrich local theories about the meaning behind the architecture of Chinese houses in Lasem. This research method uses the rationalistic paradigm with a qualitative approach. Cultural acculturation influences local architecture through variety, pattern of space, and order, so that the result of mixing culture will form a new image of local society (Fauzy, 2012). The culture acculturation has influenced the spatial layout and details of the residential houses of the Chinese community so as to produce a unique form of architecture.